Lime mortars with ceramic wastes: characterization of components and their influence on the mechanical behaviour - Matias, Gina (2014)
Considering the fundamental importance of preserving the built heritage and of ensuring the good performance achieved by incorporating ceramic particles in lime mortars in ancient times, it is important to study solutions that use materials the available today, in order to produce mortars intended to repair and replace the old ones. Solutions incorporating industrial ceramic waste might be profitable for several reasons, namely for economic, environmental and technical aspects. In this paper, seven ceramic waste products collected from ceramics factories are characterized. Their mineralogy, dimensional features and pozzolanicity were determined. Three of these products, with different particle size fractions (obtained directly from milling, dust only and fragment fractions only), were selected, incorporated into air lime mortars, and their mechanical strength was determined. In the present work, evidence of mechanical efficiency, when common sand or air lime were partially replaced by ceramic wastes, was made clear, drawing attention to the sustainability of this type of mortars, hence, encouraging further research.